Latent infection rate of potato seed tubers with Phytophthora infestans (Mont.) de Bary – an underestimated problem - Michael Zellner; Sven Keil; Marianne Benker (Journal für Kulturpflanzen, 2011)
From 2007 to 2009 applying molecular methods a total of 17 batches of seed potatoes were tested for the rates of latent infections with Phytophthora infestans (Mont.) de Bary, the pathogen of late blight. The samples were chosen randomly from different certified European seed potato productions. The average infection rate of the seed potatoes tested was 11%. The highest occurring rate was 38%. The given data show that there is no significant correlation between late blight susceptibility-levels of varieties and rates of latent infestation. There were no statistically significant differences found between seed potatoes from organic and conventional production.